Women farm what they can manage: How time constraints affect the quantity and quality of labor for married women's agricultural production in southwestern Nigeria. (April 2022) - Pierotti, Rachael S.; Friedson-Ridenour, Sophia; Olayiwola, Olubukola
Highlights: A conceptual framework linking constraints on women's time and the quantity and quality of labor available for their farms. Patterns of women's time use are rooted in common expectations regarding gender roles and responsibilities. Time constraints limit women's earnings from farming and make availability of money a determinant of what women can farm. Intrahousehold negotiations over labor and time use are about securing livelihoods and reinforcing social relationships. The conceptual framework is a tool for research on time use and gender differences in agricultural labor and productivity. Abstract: Across sub-Saharan Africa smallholder farmers depend heavily on manual labor supplied by their households, families, and communities. Gender differences in the ability of farm managers to acquire needed labor has been linked with women's disadvantage in agricultural productivity. This in-depth qualitative research in southwestern Nigeria builds on studies that document gender gaps by examining how men and women make sense of the allocation of labor within their households. Insights from observation over the course of one year and interviews with 93 participants are combined with evidence from existing literature to develop a framework that illustrates the conceptual links between constraints on women's time use and the quantity and quality of labor available for their agricultural activities. We find that women's time and labor constraints are rooted in common social expectations that men's farm plots take priority and that a woman should only farm what she can manage without interfering with the agricultural production managed by her husband. Practically, this means that women's household responsibilities and off-farm work limit their own farm labor and their ability to supervise hired labor. The prioritization of men's plots also means that labor is allocated to men's plots first in the day, which results in less labor and potentially less productive labor available for women's farms. Also, women's access to labor is especially constrained by seasonal fluctuations in labor demand because of the precedence given to men's agricultural production. The conceptual framework is meant as a tool to be used in future research on time use, agricultural labor, and gender differences in agricultural productivity. It highlights the ways in which intrahousehold negotiations over labor and time use are not just about maximizing efficiency or productivity, but also about maintaining social hierarchies, roles, and responsibilities.